2013
DOI: 10.1177/1474515113486376
|View full text |Cite
|
Sign up to set email alerts
|

Access to cardiac rehabilitation does not equate to attendance

Abstract: Results demonstrated that the majority of Australians had excellent 'geographic' access to services to support CR and secondary prevention. Therefore, it appears that it is not the distance to services that affects attendance. Our 'geographic' lens has identified that more research on socioeconomic, sociological or psychological aspects to attendance is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…Participation in CR programs after a cardiac event decreases hospital admissions, improves quality of life, morbidity and mortality [7,10,11]. Despite these proven benefits, CR programs are underutilised [8], with low participation rates internationally and in Australia [12,13], with minimal improvement over the last decade [14]. Our own research has reported only 30% of patients discharged following an acute myocardial infarction commenced a CR program within 10 weeks of discharge [15].…”
Section: Introductionmentioning
confidence: 99%
“…Participation in CR programs after a cardiac event decreases hospital admissions, improves quality of life, morbidity and mortality [7,10,11]. Despite these proven benefits, CR programs are underutilised [8], with low participation rates internationally and in Australia [12,13], with minimal improvement over the last decade [14]. Our own research has reported only 30% of patients discharged following an acute myocardial infarction commenced a CR program within 10 weeks of discharge [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the majority of these programs are implemented in rural/remote settings. Whilst mainstream chronic disease rehabilitation programs exist, they are usually specific to one particular condition and often are not accessed by Aboriginal and Torres Strait Islander people [21]. Greater uptake and outcomes have been reported when programs are delivered within an Aboriginal and Torres Strait islander community-controlled health service with opportunity for "yarning" (talking informally) and tailored exercise [22].…”
Section: Introductionmentioning
confidence: 99%
“…5 Reasons attributed to non attendance have been researched extensively 6,7 and include non-referral, location of CR programs, work or family commitments, distance and travel time 8 and negative beliefs pertaining to the value of CR programs. 9 While most people living in metropolitan areas have a choice to attend hospital or outpatient CR, 10 patients who reside in rural areas often have difficulty in accessing CR services. Research highlights the importance of improving CR accessibility to rural patients 5 as they are more likely to die from cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Improving accessibility has the potential to provide more patients with the benefits of CR. While it has been reported that the majority of Australians live within 60 minutes of CR services, 10 others propose that telehealth services may improve cardiac health outcomes for persons unable to access metropolitan based CR services due to their remoteness. 16 The Aussie Heart Guide Program (AHGP) represents a new model of CR service delivery in Australia 17,18 It aims to offer patients with CHD and who cannot attend hospital based CR services access to CR.…”
Section: Introductionmentioning
confidence: 99%